Sex difference determined the role of sex hormone-binding globulin in obese children during short-term weight reduction program. Issue 19 (May 2017) - Wang, Fu-Min; Lin, Chien-Ming; Lien, Shao-Hung; Wu, Li-Wei; Huang, Ching-Feng; Chu, Der-Ming
Abstract : Abstract: The relationship between hyperinsulinemia and decreased sex hormone-binding globulin (SHBG) levels has been observed in obese adults and children. Weight reduction not only increased insulin sensitivity but also elevated serum SHBG levels in obese adults and children. However, the correlation between the changes in insulin resistance indices and serum SHBG concentration during weight reduction program (WRP) is not fully understood, particularly in obese children. This study is to evaluate whether SHBG level is a potential biomarker that can be used to assess insulin resistance in obese children during a short-term WRP. Forty-eight obese Taiwanese children (11.7 ± 2.2 years; 25 boys and 23 girls) participating in 8-week WRP were studied. Anthropometric measurements, lipid profiles, insulin resistance indices, and serum SHBG concentration were recorded at baseline and at the end of the WRP. The results showed body weight (BW), body mass index (BMI), body fat percentage (BF%), body fat weight (BFW), and insulin resistance indices such as fasting insulin, fasting insulin to glucose ratio, homeostasis model assessment (HOMA) of insulin resistance, log (HOMA) all significantly decreased after the 8-week WRP. With respect to lipid profiles, only high-density lipoprotein cholesterol (HDL-C) levels increased in both sexes. At baseline, insulin resistance indices were inversely correlated with SHBG concentrations in girls, but not in boys. The difference in SHBG after WRP was 2.58 nmol/L (95% confidence interval [CI]: −3.51, 8.66) in boys and 0.58 nmol/L (95% CI: −5.23, 6.39) in girls. There was a trend toward increased serum SHBG levels in boys ( P  = .39) and girls ( P  = .84) after weight loss, but a significantly negative correlation between the change in SHBG and in each of the insulin resistance indices only in the girls after adjusting age and ΔBFW during WRP. In conclusion, short-term WRP has the potential effects of decreased BW, BMI, BF%, and BFW, as well as increased serum HDL-C levels and insulin sensitivity in obese Taiwanese children. Although serum SHBG levels moderately increased in both sexes during short-term WRP, measuring the change in SHBG concentrations might be a potential biomarker to evaluate improvement in insulin resistance in girls only, and not in boys.